Social movements and culture of rights - Cáceres Valdivia, Eduardo (1999)
Throughout the 20th century, Peruvian social organizations have been the protagonists of several stories. One of them, unfortunately seldom highlighted, is the history of the conquest of rights and citizenship, not only for them, but for the whole of Peruvian society. Particularly tortuous was the process of conquest of rights in rural Andean societies. Not in vain did they act in scenarios that were the 'strategic reserve' of domination and exclusion.